DNMT and HDAC inhibitors induce cryptic transcription start sites encoded in long terminal repeats - Brocks, David; Schott, Johanna; Oehme, Ina; Witt, Olaf; Mallm, Jan-Philipp; Rippe, Karsten; Stoecklin, Georg (Nature genetics, 2017)
Several mechanisms of action have been proposed for DNA methyltransferase and histone deacetylase inhibitors (DNMTi and HDACi), primarily based on candidate-gene approaches. However, less is known about their genome-wide transcriptional and epigenomic consequences. By mapping global transcription start site (TSS) and chromatin dynamics, we observed the cryptic transcription of thousands of treatment-induced non-annotated TSSs (TINATs) following DNMTi and HDACi treatment. The resulting transcripts frequently splice into protein-coding exons and encode truncated or chimeric ORFs translated into products with predicted abnormal or immunogenic functions. TINAT transcription after DNMTi treatment coincided with DNA hypomethylation and gain of classical promoter histone marks, while HDACi specifically induced a subset of TINATs in association with H2AK9ac, H3K14ac, and H3K23ac. Despite this mechanistic difference, both inhibitors convergently induced transcription from identical sites, as we found TINATs to be encoded in solitary long terminal repeats of the ERV9/LTR12 family, which are epigenetically repressed in virtually all normal cells.